2010
DOI: 10.1111/j.1574-695x.2010.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms associated with biliary stent clogging

Abstract: Endoscopic stenting is a palliative approach for the treatment of diseases involving biliary obstruction. Its major limitation is represented by stent occlusion, followed by life-threatening cholangitis, often requiring stent removal and replacement. Although it has been suggested that microbial colonization of biliary stents could play a role in the clogging process, the so far available data, particularly on the role of anaerobic bacteria, are not enough for a comprehensive description of this phenomenon. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
0
40
1
1
Order By: Relevance
“…We think that this was due to the rough and uneven surface of e-PTFE which may create niches on which sludge can accumulate. Previous studies have suggested that the degree of surface smoothness is related to development of biofilm [20]. However, in this study, no stent occlusion by sludge clogging during bile exposure was observed in any of the metallic stents for at least 6 months.…”
Section: Discussioncontrasting
confidence: 67%
“…We think that this was due to the rough and uneven surface of e-PTFE which may create niches on which sludge can accumulate. Previous studies have suggested that the degree of surface smoothness is related to development of biofilm [20]. However, in this study, no stent occlusion by sludge clogging during bile exposure was observed in any of the metallic stents for at least 6 months.…”
Section: Discussioncontrasting
confidence: 67%
“…Finally, prosthetic devices can host biofilms that cause chronic infections and other symptoms (1,2). In particular, biliary stents regularly clog due to slime made up of cholesterol and multispecies biofilms that include P. aeruginosa (50). We found that biofilm streamers develop on bare-metal stents within 12 h after inoculation, and span the gaps in the wire mesh (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Among 19 anaerobes recovered from 16 stents were Clostridium perfringens , C. bifermentans and B. fragilis . Twenty-eight obstructed biliary stents explanted from patients after a mean dwell time of 164 days were examined by conventional anaerobic culture, and the central areas of the obstructing sludge underwent DNA extraction and PCR-based identifi cation ribosomal RNA amplifi cation and sequencing (Guaglianone et al 2010 ). Five species were identifi ed on the basis of PCR analysis: Atopobium rimae , Bifi dobacterium breve , Bilophila wadsworthia , Mogibacterium diversum , and Peptostreptococcus stomatis .…”
Section: Biofi Lm Studies Of Anaerobic Organismsmentioning
confidence: 99%